1983
DOI: 10.1507/endocrj1954.30.319
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the preovulatory release of gonadotropins and prolactin by spinal transections in female rats.

Abstract: The effect of spinal transections on the preovulatory release of gonadotropins and PRL was investigated in female rats. A preovulatory rise in serum LH, FSH and PRL and subsequent ovulation were prevented by complete spinal transections (CST) at high thoracic levels (T3-T7), but not at low thoracic and lumbar levels (T8-L5), performed at 1000-1230 h on proestrus.Norepinephrine (NE) concentrations in the preoptic-anterior hypothalamic area at 1700-1800 h on proestrus were also significantly reduced by CST at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Suckling or mammary stimulation increases PRL secretion (Noel et al, 1974;Herman et al, 1981;Reichlin, 1992). In animal experiments, transection of the spinal cord at T3-T7, particularly bilateral transection of lateral column of spinal cord, blocks mammary stimulation of PRL release (Nishihara et al, 1983). No change in PRL release is found in lesions of the spinal cord at T8-L5.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Suckling or mammary stimulation increases PRL secretion (Noel et al, 1974;Herman et al, 1981;Reichlin, 1992). In animal experiments, transection of the spinal cord at T3-T7, particularly bilateral transection of lateral column of spinal cord, blocks mammary stimulation of PRL release (Nishihara et al, 1983). No change in PRL release is found in lesions of the spinal cord at T8-L5.…”
Section: Discussionmentioning
confidence: 95%
“…The tumour might have directly stimulated the afferent nerve fibres of intercostal nerves. The tumour also compressed the spinal cord, but this was not the cause of the increased PRL secretion, since transection of spinal cord at T8 or below has no effect on prolactin secretion (Nishihara et al, 1983). Wang et al (1992) reported that hyperprolactinaemia was seen in 17 of 63 patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%